Healthy Eating: Folate - Linda B. Bobroff (EDIS)
Folate is one of the B vitamins. It is involved in the formation of DNA and amino acids. DNA is the genetic material found in all cells of your body. Amino acids are the building blocks of proteins. Learn more about this important vitamin in this revised 2-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, December 2010.